Bacteroides fragilis ameliorates Cronobacter malonaticus lipopolysaccharide-induced pathological injury through modulation of the intestinal microbiota - Ling, Na; Zhang, Xiyan; Forsythe, Stephen; Zhang, Danfeng; Shen, Yizhong; Zhang, Jumei; Ding, Yu; Wang, Juan; Wu, Qingping; Ye, Yingwang (Frontiers in Immunology, 2022)
Cronobacter has attracted considerable attention due to its association with meningitis and necrotizing enterocolitis (NEC) in newborns. Generally, lipopolysaccharide (LPS) facilitates bacterial translocation along with inflammatory responses as an endotoxin; however, the pathogenicity of Cronobacter LPS and the strategies to alleviate the toxicity were largely unknown. In this study, inflammatory responses were stimulated by <uri xlink:href="http://www.baidu.com/link?url=rWZJVQ-G07obrxEvZ2a1IItiyB4FHCqmHIqX8wwAXJurAHG8hFjYb8ln6TZyvGSRS24ugF9JDQ4E2HqxAx59riyGWejRr1l09C2RSHKxyGfYCBusW8k-oGHtfkt8tA8F" xmlns:xlink="http://www.w3.org/1999/xlink">intraperitoneal injection of Cronobacter malonaticus LPS into Sprague–Dawley young rats. Simultaneously, Bacteroides fragilis NCTC9343 were continuously fed through gavage for 5 days before or after injection of C. malonaticus LPS to evaluate the intervention effect of B. fragilis. We first checked the morphological changes of the ileum and colon and the intestinal microbiota and then detected the generation of inflammatory factors, including tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and interleukin-10 (IL-10) and the expression of Toll-like receptor 4 (TLR4), occludin, claudin-4, and iNOs. The results indicated that C. malonaticus LPS exacerbated intestinal infection by altering gut microbe profile, tight junction protein expression, and releasing inflammatory factors in a time- and dose-dependent manner. Intriguingly, treatment with B. fragilis obviously diminished the pathological injuries and expression of TLR4 caused by C. malonaticus LPS while increasing gut microbes like Prevotella-9. We note that Shigella, Peptoclostridium, and Sutterella might be positively related to C. malonaticus LPS infection, but Prevotella-9 was negatively correlated. The results suggested that the intestinal microbiota is an important target for the prevention and treatment of pathogenic injuries induced by C. malonaticus LPS.